Manufacturing Methods, Microstructural and Mechanical Properties Evolutions of High-Entropy Alloys: A Review - Alshataif, Yaser A.; Sivasankaran, S.; Al-Mufadi, Fahad A.; Alaboodi, Abdulaziz S.; Ammar, Hany R. (Metals and materials international, 2020)
High entropy alloys (HEAs) are being attracted recently by several researchers, scientists, and academicians to achieve extraordinary and outstanding properties that cannot be obtained from conventional alloys. HEAs are multicomponent alloys in which a minimum of five metallic elements are mixed in an equal molar or non-equal molar ratio. The rapid growth of this field produces a huge amount of scientific papers over the last decade. However, still, there is a need to review various manufacturing methods and their results. Also, the outcome of the scientific articles related to HEAs has ignored the various methods of synthesizing and manufacturing. In this review article, an attempt was made and largely concentrated on the methods and techniques that can be used in the manufacturing and synthesizing of the HEAs. Recently, the properties of HEAs become much better when compared to conventional alloys. Some techniques have succeeded in producing ultrafine microstructure grains which become a leap in industrial fields. Now, the manufacturing methods of conventional alloys are almost familiar and implemented according to the suggestions given by the researchers and academicians based on their work. Therefore, the present review article has demonstrated various methods of manufacturing of HEAs with novel schematics with a preview description for more understanding of the basic work criteria. Besides, this article has reviewed the outcomes of several research articles related to several methods, then compared the outcome of each method with the corresponding mechanical properties, and major challenges of HEAs are discussed and reported. Graphic Abstract